Here is the process of how I did it:
Step 1: Make this equation : 2x+4y = 20 equal x by isolating x and bring everything else on the right side of the equation
2x + (4y-4y) = 20 - 4y
2x = 20 - 4y
![(2x)/(2) = (20 - 4y)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/e2y30t4tc5f7od4iwyjozizw5ldm1k7y03.png)
x = 10 - 2y
Step 2: In the other equation given (3x+2y=26) every time you see an x replace it with the equation solved above (x = 10 - 2y). This will help you find the y
3x+2y=26 ---> 3(10 - 2y)+2y=26
10(3) - 2y(3) + 2y = 26
30 - 6y + 2y = 26
(30-30) - 4y = (26 - 30)
![(-4y)/(-4) =(-4)/(-4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9tbhobd0ii8s4ewidrq9hyrsda4u7em7u0.png)
y = 1
Step 3: In the equation you found in step 1 (x = 10 - 2y) plug 1 into all the y's so you can find x
x = 10 - 2y ---> x = 10 - 2(1)
x = 10 - 2
x = 8
Hope this helped!